Decoration and Use of Carya Speciees Planting in Urban Gardening - V.O. Bozhok (Науковий вісник НЛТУ України, 2017)
The main structural component of the park landscape is the tree and shrub vegetation. Carya is the species that depends a lot on growing conditions. An objective assessment of this species can be given only during long-term observations, including the full range of decorative features. The author aimes at conducting complex estimation of decoration of six Carya species introduced on Ukraine's territory with the purpose of their usage in urban gardening. In the course of research we have revealed that Carya laciniosa Loud and Carya ovata K. Koch give the best decoration. These two kinds in comparison with others differ in decoration foliage, that hang on trees in the autumn period for a long time and condition bark, that exfoliates on trees of the senior age and hangs as longitudinal strips during all year. Carya cordiformis K. Koch provides lower decoration that is characterized by fine fruits and short-term to decrease foliage. It is necessary to note high resistance to air pollution in conditions of large cities, and also high bactericidedion, which is also characteristic for other kinds of Nut family. Carya root system behind the linear and volumetric sizes partly exceeds its top part. Such advanced root system not only provides high wind stability, but also promotes uniform receipt of nutritious substances up to a crone. It positively influences qualitative formation of wood, which differs by identical thickness of a year ring. To conclude, Carya property to develop powerful root system promotes to its wind steadiness. The separate kinds of Carya well renew also by natural way. Young sowing under flat age trees differ by weak growth, but landed on an open place, give a good gain per the first years. Such vegetation posterity with success can be used also in urban conditions for creation of certain landscape compositions. Such sowing requires additional growing up till 5-6 years with formation of root system and crone.